Duchene Muscular Dystrophy: Pathogenesis, Pathophysiology, Diagnosis Management to Therapy. - Sharma, Bharti; Devi, Savita; Singh, Kamaldeep (Asian Journal of Pharmaceutical Research and Development, 2020)
Duchene muscular dystrophy (DMD) is a neuromuscular inherited disease which deal with X-linked occurs due to mutations in the dystrophin gene. The characterisation achieved by progressive muscle weakness in all our the body specially in legs and arms and wasting due to the absence of dystrophin protein which further causes degeneration of different types of muscules such as skeletal and cardiac. Gene mutation is one of the major causes for Duchenne muscular dystrophy located in cytoskeletal protein dystrophin. The diagnosis can be start up with careful review of the physical condition, history and examination of body organs and developmental delay, proximal weakness in muscules, and elevated biochemical compound serum creatine kinase, plus other confirmatory test like muscle biopsy or genetic testing. To improve the life expectancy of patient the early use of exercises, diet & nutrition management and other supportive strategies has been implemented. Moreover, uncontrolled condition can be treated with gene therapy with the use of plasmids or viruses, mutations and short DNA fragments can be corrected, oligonucleotides are first line treatment for exon skipping of mutations. Myoblasts or stem cells replacement therapy can be apply to reproduction of muscules.